Explorative Study Of Adverse Drug Reactions And Drug-Resistant Tuberculosis Among Tuberculosis Patients In Hospital Pulau Pinang, Malaysia - Kurniawati, Fivy (2013)
Tuberculosis, an infectious disease caused by Mycobacterium tuberculosis claimed for human life throughout history today become second leading infectious diseases caused death after HIV-AIDS. Treatment of tuberculosis required combination of anti-tuberculosis drug. Anti-tuberculosis adverse drug reactions (ADRs) become important as longer use of these drugs. In addition to antituberculosis ADRs, the presence of tuberculosis bacteria that resistant to anti tuberculosis drug may complicate on tuberculosis treatment. This study was a retrospective cross-sectional observation study. Research subjects of this study were patients who were treated as active tuberculosis in Chest Clinic, Hospital Pulau Pinang, Malaysia. The aim of the study was to investigate anti-tuberculosis ADRs, drug-resistant tuberculosis (DR-TB), and all associate factors related to ADRs and DR-TB, also patients’ treatment clinical outcomes. Adverse drug reactions were detected from patients’ complains, clinical symptom, laboratory test result, and any other related information and DR-TB detected from patients’ sensitivity test result. Patients’ socio-demographic, medical history, tuberculosis diagnosis and treatment, clinical sign and symptom of ADRs, laboratory test result, sputum smear test, radiology test result, and other relevant information were collected. Obtained data then exported to excel and analyzed by using Statistical Package for Social Sciences (SPSS® version 15).